Uses, Motivation, and Innovation Readiness’ Gratification of Young Adults’ Streaming Application in Indonesia and Malaysia - Nurafni Rubiyanti; Alex Winarno; Mokhtarrudin Ahmad; Mahir Pradana; Hussein Gibreel Musa (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The rapid development of digital technology has brought significant changes in communication, learning, and media consumption patterns, particularly in Malaysia and Indonesia. These changes have been further accelerated by the COVID-19 pandemic, which has emphasized the crucial role of digital platforms in everyday life. Ease of access and increasingly affordable internet-based devices have driven a shift from Free-To-Air (FTA) television to on-demand digital television and streaming services. This study aims to examine the influence of motivation, readiness for innovation, and gratification factors on the adoption and usage patterns of digital television in both countries. The research method used is a quantitative approach, referring to Uses and Gratifications Theory (UGT) and the concept of Absorptive Capacity (ACAP), while also considering socio-demographic and socio-cultural characteristics such as income level, education, and age. The results show that user motivation, readiness for innovation, and satisfaction levels significantly influence decisions to use digital television and streaming services. In conclusion, these findings provide important insights for stakeholders in formulating strategies for developing the digital broadcasting ecosystem in Southeast Asia.